Tecnologias digitais da informação e comunicação (TDICs): uma análise dos egressos de um curso de Pedagogia EAD sobre o uso dessas ferramentas na formação e atuação profissional - Araujo, Giovanna Cristina Stoppa (Universidade Federal de São Carlos, 2020)
This study look for to contribute with the growing of searches in the area and investigate the importance about the ICDT in formation of futures teachers, according to the question: How the distance education courses of Pedagogy preperes the futures teachers for works with ICDT in the classroom? In this way, the aim of this study is explore and analyse the uses of Information and Communication Digital Technologies (ICDT) in Pedagogy courses in distance education modality and the result of this process in actuation of begining teachers. The search specific objective is analyse the importancy about the learning of Information and Communication Digital Technologies (ICDT) in the distance education courses; investigate the teachers’ knowledge related with the Information and Communication Digital Technologies (ICDT) and the contribition of these tools for the teaching. This qualitative investigation was realize according to an exploratory and descritive study through application of online qustionary with 27 teachers of the Basic Education graduated in the UBA UFSCar distance education courses of Pegagogy. These serch’s data was consult and was made charts with the result based in the discution and the organization of four groups: Identitary profile and formation processes; ICDT and beginning formation; ICDT and professional actuation; ICDT and professional perceptions. The results of the analyses point to a training that allows the use of ICDT troughout the under graduate course, reiforcing the importance of using there tools for the teaching and learning process. They also reveal that the students in the distance education course are mostly professional who had already mastered the ICDT before entering the courses, so they understood the meaning and importance of the ICDT for training and professional performace, they value the contributions of the distance education course in the mobilization these tools and point out the resistance of peers to use them due to the lack of training and mastery in the area.
Digital information and technologies (ICDT) and analysis of egress from an UBA Pedagogy course on the use of these tools in training and profissional performance
Keywords: Pedagogia EaD; TDICs; Formação inicial; Atuação profissional; Distance education; ICDT; Beginning formation; Professional actuation; CIENCIAS HUMANAS::EDUCACAO